ریاست میں سماجی حقوق کاتحفظ :سیرتِ نبیﷺ کی روشنی میں تجزیاتی مطالعہ: Protection of Social Rights in the State: An Analytical Study in the Light of Sirah - DR. Noor Hayat Khan,; Sara Noor, (MEI, 2025)
This paper explores a three-dimensional study of social welfare and cohesion: the legal protection of social rights, the awareness and recognition of social responsibilities, and the significance of social ethics. The legal aspect emphasizes the role of constitutional and legislative frameworks in safeguarding fundamental rights such as education, healthcare, employment, and justice. These laws serve as mechanisms to ensure equity and justice within society. The second dimension highlights the importance of individuals’ and institutions’ awareness of their responsibilities toward others. A socially responsible attitude enhances solidarity, mutual support, and collective growth. Finally, the ethical perspective underscores the role of moral values—such as honesty, tolerance, and justice—in nurturing a just and harmonious society. Together, these dimensions form the foundation of a stable and humane social structure where rights are protected, duties are understood, and ethical conduct is promoted.